Subanesthetic dose of ketamine decreases prefrontal theta cordance in healthy volunteers: implications for antidepressant effect - Horacek, J; Brunovsky, M; Novak, T; Tislerova, B; Palenicek, T; Bubenikova-Valesova, V; Spaniel, F; Koprivova, J; Mohr, P; Balikova, M; Hoschl, C (Psychological medicine, 2010)
BACKGROUND: Theta cordance is a novel quantitative electroencephalography (QEEG) measure that correlates with cerebral perfusion. A series of clinical studies has demonstrated that the prefrontal theta cordance value decreases after 1 week of treatment in responders to antidepressants and that this effect precedes clinical improvement. Ketamine, a non-competitive antagonist of N-methyl-D-aspartate (NMDA) receptors, has a unique rapid antidepressant effect but its influence on theta cordance is unknown. METHOD: In a double-blind, cross-over, placebo-controlled experiment we studied the acute effect of ketamine (0.54 mg/kg within 30 min) on theta cordance in a group of 20 healthy volunteers. RESULTS: Ketamine infusion induced a decrease in prefrontal theta cordance and an increase in the central region theta cordance after 10 and 30 min. The change in prefrontal theta cordance correlated with ketamine and norketamine blood levels after 10 min of ketamine infusion. CONCLUSIONS: Our data indicate that ketamine infusion immediately induces changes similar to those that monoamineric-based antidepressants induce gradually. The reduction in theta cordance could be a marker and a predictor of the fast-acting antidepressant effect of ketamine, a hypothesis that could be tested in depressive patients treated with ketamine.
Keywords: afekt; Ketamine; Prefrontal Cortex; Anesthetics, Dissociative; klinické křížové studie; prefrontální mozková kůra; Humans; Theta Rhythm; Double-Blind Method; Predictive Value of Tests; ketamin; Female; dospělí; dvojitá slepá metoda; lidé; elektroencefalografie; Biomarkers; Affect; Adult; theta rytmus EEG; biologické markery; ženské pohlaví; Depressive Disorder; Male; depresivní poruchy; prediktivní hodnota testů; Electroencephalography; Cross-Over Studies; mužské pohlaví; anestetika disociativní